Implikasi Hukum Putusan Mahkamah Konstitusi terhadap Pengujian Undang-Undang yang Bersifat Bersyarat - Aris Prasetyo; Aturkian Laia (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The Constitutional Court (MK) developed conditional decisions (conditionally constitutional and conditionally unconstitutional) as a judicial innovation to prevent legal vacuums. However, this model triggers implementation challenges and legal uncertainty. This normative juridical research analyzes the status, legal implications, and implementation issues of conditional decisions within the national legal system. The results indicate that conditional decisions expand MK’s role into an active constitutional norm interpreter. On one hand, it offers proportional constitutional protection. On the other hand, abstract conditions, delayed legislative follow-ups, and misinterpretations among law enforcers undermine legal certainty. Therefore, the effectiveness of conditional decisions demands clear dictates, methodological consistency, and serious compliance from state institutions.